Effect of Diatomaceous Biosilica and Talc on the Properties of Dielectric Elastomer Based Composites - Ewa Olewnik-Kruszkowska; Weronika Brzozowska; Arkadiusz Adamczyk; Magdalena Gierszewska; Izabela Wojtczak; Myroslav Sprynskyy (Energies, 2020)
Currently, scientists are still looking for new polymeric materials characterized by improved mechanical, thermal as well as dielectric properties. Moreover, it should be stressed that new composites should be environmentally friendly. For this reason, the aim of this work is to establish the influence of natural fillers in the form of diatomaceous biosilica (B) and talc (T) on the properties of dielectric elastomer (DE)-based composites. The dielectric elastomer-based materials have been tested taking into account their morphology, thermal and mechanical properties. Moreover, the dielectric constant of the obtained materials was evaluated. Obtained results revealed that the presence of both diatomaceous biosilica and talc significantly increases dielectric properties while having no significant effect on the mechanical properties of the obtained composites. It should be stressed that the performed analyses constitute a valuable source of knowledge on the effective modification of the thermal and dielectric properties of newly obtained materials.